2008
DOI: 10.1373/clinchem.2008.108845
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Single Assay for Both Type III and Type VI TMPRSS2:ERG Fusions in Noninvasive Prediction of Prostate Biopsy Outcome

Abstract: BACKGROUND: TMPRSS2:ERG fusions are promising prostate cancer biomarkers. Because they can occur in multiple forms in a single cancer specimen, we developed a quantitative PCR test that detects both type III and type VI TMPRSS2:ERG fusions. The assay is quantified from a standard curve determined with a plasmid-cloned type III TMPRSS2:ERG fusion target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…Two other studies investigated TMPRSS2:ERG fusion in urine and reported similarly high specificities of 93% and 73%, respectively; and one study evaluated TMPRSS2:ERG fusion in expressed prostatic secretions reporting a specificity of 80%. 23 However, prior studies have not evaluated the utility of combining serum PSA test results with noninvasive detection of TMPRSS2:ERG and PCA3 in developing models to predict prostate cancer diagnosis in a clinically relevant context, as we explored in this study.…”
Section: Commentmentioning
confidence: 99%
“…Two other studies investigated TMPRSS2:ERG fusion in urine and reported similarly high specificities of 93% and 73%, respectively; and one study evaluated TMPRSS2:ERG fusion in expressed prostatic secretions reporting a specificity of 80%. 23 However, prior studies have not evaluated the utility of combining serum PSA test results with noninvasive detection of TMPRSS2:ERG and PCA3 in developing models to predict prostate cancer diagnosis in a clinically relevant context, as we explored in this study.…”
Section: Commentmentioning
confidence: 99%
“…Because a diagnostic strategy based on prostate tissue is inadequate for clinical application, noninvasive methods, similar to those for PCA3 (18 ), were developed to detect the fusion transcripts in urine (19 -23 ) voided after digital rectal examination (DRE). In contrast with a very high diagnostic specificity (Ͼ90%) and a very good predictive value for positive biopsy, the overall diagnostic sensitivity of the test was reported to be only around 50%, although it could be improved by combining results with PSA, DRE (21 ), and PCA3 (20,23 ). One drawback of those studies was the inability to match findings in urine with those in prostate tissue in the same patient.…”
mentioning
confidence: 99%
“…Several studies have indicated that TMPRSS2 -ERG fusions confer a worse prognosis (Nam et al, 2007;Attard et al, 2008a;Clark et al, 2008), whereas others have not . Discrepancies in the reported prognostic significance of TMPRSS2 -ERG fusions can be explained in a similar manner by factors affecting the variation in prevalence of TMPRSS2 -ERG (i.e., cohort race/ethnicity, fusion detection technique), and are also liable to the primary end point of the study (i.e., biochemical recurrence, overall survival).…”
mentioning
confidence: 99%